Analisis Terhadap Proyek Food Estate dalam Penggunaan Lahan Hutan dan Ketahanan Pangan Ditinjau dari Perspektif Hukum Lingkungan (International Forum of Researchers and Lecturers, 2024)
The Food Estate project in Indonesia aims to enhance food security. However, it has resulted in significant environmental impacts through the conversion of forests into agricultural land. Particularly, the peat ecosystem is vulnerable, threatening the natural balance and environmental sustainability. In evaluating the project's impact, this research adopts a normative legal approach focusing on literature analysis. Research findings indicate that land conversion for Food Estate sacrifices crucial environmental aspects, such as vulnerable peatlands prone to fires and soil quality degradation. Policy alternatives, such as agricultural diversification and ecosystem protection, are proposed as solutions to support food security without harming the environment. The conclusion of this study emphasizes the need for stricter environmental law enforcement between the government and community participation in decision-making to ensure the sustainability of agricultural projects like the Food Estate.